Carbon risk management and corporate competitive advantages: “Differential promotion” or “cost hindrance”? - Zhou, Zhifang; Zhang, Lingyan; Lin, Li; Zeng, Huixiang; Chen, Xiaohong (Business strategy and the environment, 2020)
Given the strengthening of carbon regulations and the launch of emission trading scheme in China, companies are facing tremendous pressure to reduce carbon emissions, suggesting the necessity of understanding whether carbon risk management may affect corporate financial benefits. Therefore, this paper empirically demonstrates the influence of carbon risk management on corporate competitive advantages. We find that the relationship between carbon risk management and corporate competitive advantages is a “kuznets curve” that exists only among firms with weak product competition. And this relationship tends to be weakened in firms with a distant administrative hierarchy. We conclude that the influence of low carbon management on corporate competitive advantages is complicated and subject to the firm's political relevance.